ANALISIS FIKIH TERHADAP HAKIKAT OPEN MARRIAGE DAN STATUS HUKUMNYA - Tresna Samudra; Akhmad Husaini (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study examines the practice of open marriage from the perspective of Islamic jurisprudence as a form of consensual non-monogamous relationship between legally married spouses. The method employed is qualitative, using a library research approach with descriptive-analytical analysis and textual criticism within the framework of uṣūl al-fiqh. The analysis follows several methodological stages: taṣwīr al-mas’alah (conceptual framing), takyīf al-fiqhī (legal classification), taḥqīq al-manāṭ (validation of legal cause), and istinbāṭ al-ḥukm (derivation of ruling), based on sources from the Qur’an, ḥadīth, scholarly consensus (ijmāʿ), and both classical and contemporary fiqh literature. The findings indicate that open marriage does not fulfill the essential conditions of lawful intimate relations in Islam and resembles pre-Islamic marriage practices abrogated by the Prophet ﷺ. Based on legal maxims such as al-aṣl fī al-abḍāʿ al-taḥrīm and al-ḍarar lā yuzāl bi al-ḍarar, it is classified as zinā muḥarram and al-fawāḥish. Within the framework of maqāṣid al-sharīʿah, it contradicts the preservation of dignity (ḥifẓ al-ʿird), lineage (ḥifẓ al-nasl), and religion (ḥifẓ al-dīn). Academic arguments supporting CNM, emphasizing freedom and consent, are critically assessed as inconsistent with Islamic values. Therefore, open marriage is deemed absolutely prohibited under Islamic law.